Midlife-Aged Woman: The Effect of Work-Family Conflict on Life Satisfaction in Dual-Earner Families - Zefanya, Harita Julie; Simanjuntak, Megawati; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
A dual-earner family is a condition where the husband and wife work outside the home and also take care of the children at home simultaneously to fulfill the family's needs. Families in middle age undergo significant transitions, affecting both their external and internal dynamics. This research aims to analyze the impact of work-family conflict on the life satisfaction of working middle-aged families. This research was conducted using a purposive sampling with a questionnaire in Greater Jakarta. This study was conducted from July to August 2024. Data analysis was performed using SMART-PLS 3 to investigate the influence between variables. This research involved 99 women aged 46-50 years (middle age), and worked outside the home with productive working hours (7-8 hours a day). The results show that the majority of wives who work in middle age can handle work-family conflict and have good life satisfaction. The SEM analysis reveals that the higher the work-family conflict, the lower a person's life satisfaction in the family will be. This research strengthens the structural-functional theory which states there must be a homeostasis principal to maintain their respective roles in the family. This study implies that working families need to maintain a balance between work and life to enhance overall family well-being.